WOMEN'S STUDY ON RANDAI SI RABUANG AMEH, AS AN EXISTENCE OF RANDAI DEVELOPMENT IN MINANGKABAU - Monita Precillia; Dedi Darmadi (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
This article entitled